Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s00066-010-2088-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of “Late” and “Early” Prophylactic Cranial Irradiation in Patients with Limited-Stage Small Cell Lung Cancer

Abstract: PCI significantly decreases the incidence of brain metastases and delays their development in patients with LS SCLC. "Early" PCI is more effective than PCI applied after combined therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…A phase II study revealed that the incidence of brain metastasis was 7.3% in the early PCI group, when PCI was performed during chemoradiotherapy, and 20% in the late PCI group, when PCI was performed following chemoradiotherapy (P=0.00901). Consequently, the timing of PCI was hypothesized to be an important factor for decreasing the incidence of brain metastases (10). However, the increased risk of long-term neurotoxicity should be considered when PCI is used concurrently with chemotherapy (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase II study revealed that the incidence of brain metastasis was 7.3% in the early PCI group, when PCI was performed during chemoradiotherapy, and 20% in the late PCI group, when PCI was performed following chemoradiotherapy (P=0.00901). Consequently, the timing of PCI was hypothesized to be an important factor for decreasing the incidence of brain metastases (10). However, the increased risk of long-term neurotoxicity should be considered when PCI is used concurrently with chemotherapy (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results from Auperin et al were from a subgroup analysis and should be interpreted with caution. Two prospective randomized studies comparing the optimal timing of PCI revealed conflicting conclusions; an early randomized study revealed no difference in the frequency of brain metastases between PCI performed at the start of induction treatment and PCI delivered 6 weeks later, whereas a later study demonstrated a statistically significant decrease in intracranial recurrence when PCI was performed during chemoradiotherapy as opposed to following chemoradiotherapy (9,10). Therefore, the optimal timing of PCI delivery should be established.…”
Section: Introductionmentioning
confidence: 99%
“…Because of that, the brain is considered the first site of recurrence in an aggressive tumor such as SCLC. Many randomized studies showed that in patients with LD-SCLC exhibiting CR after CRT, PCI reduces the incidence of brain metastasis and improves survival rate [2,[9][10][11][12]. Timing of PCI is a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Timing of PCI is a matter of debate. There was a tendency toward a decrease in the incidence of brain metastasis with early PCI [2,12]. However, early PCI is not possible in all patients for various reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of 30 Gy in 2-Gy daily fractions of PCI delivered after completion of chemoradiotherapy ("late" arm) and after thoracic radiotherapy but prior to the last cycle of chemotherapy ("early" arm) demonstrated that early PCI was associated with better outcome [22]. A recent intergroup phase III randomized study of 25 or 36 Gy PCI in 720 patients with limited-stage SCLC compared survival, intracranial tumor control, quality of life measures, and neurocognitive outcomes.…”
Section: Prophylactic Cranial Irradiationmentioning
confidence: 99%